The psychometric properties of the DAIMON Scale, a translation from Spanish to English: an instrument to measure the relationship with and between voices. Issue 1 (2nd January 2020) - Rosen, Cherise; Chase, Kayla A.; Perona-Garcelán, Salvador; Marvin, Robert W.; Sharma, Rajiv P.
ABSTRACT: With recent emphasis placed on altering the relationship between the hearer and their voice(s) to decrease levels of distress, there is an increased need for psychological measures to evaluate clinical intervention outcomes. Currently, there are few such measures available. The DAIMON scale is designed to evaluate the dialogical aspects of the relationship of person to voice, voice to person, the emotional salience of this relationship and the dialogic relationship between voice(s). The purpose of the current study was to translate and adapt the DAIMON from Spanish to English and measure its psychometric properties for future use in a clinical population. Forty-four persons currently experiencing voices participated. The DAIMON ~ English version (DAIMON-EV) demonstrated acceptable reliability and validity indices. The psychometric properties of the DAIMON-EV were found to be reliable, with the overall internal consistency of the measure and all subscale ordinal α scores ranging from 0.89 to 0.94. Concurrent validity of the DAIMON-EV was examined by the relation to the internal constructs of the PSYRATS-AVHs, VAY and the BAVQ-R. The integrity of the measure was maintained, and all items of the DAIMON-EV were shown to be a reliable measure of the assigned construct.